Implementasi Model Keperawatan Berbasis Manajemen Pengetahuan dalam Meningkatkan Kepatuhan Pengobatan Tuberkulosis Paru - Wahyuni Lestari, Ayu; Meti Kody, Martha; Noviana, Ineke; Ramadhan, Nur (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Pulmonary tuberculosis (TB) remains a major public health issue in Indonesia. Treatment adherence is a key challenge, especially in Emergency Departments (EDs), where time and resources are limited. A knowledge management-based nursing model has emerged as an innovative strategy to improve patient education and engagement in TB treatment.A literature review was conducted using Google Scholar, with keywords: pulmonary tuberculosis, treatment adherence, nursing model, knowledge management, and emergency department. From an initial 17,400 articles, 407 were selected based on inclusion criteria. Ten key studies published between 2021–2025 were thematically analyzed. The implementation of a knowledge management-based nursing model in ED settings significantly improved TB treatment adherence. Interventions such as telenursing, nurse training, health coaching, and digital technologies (video-DOT, mobile applications) enhanced patient understanding and strengthened nurse-patient communication. Training also improved nurses’ educational behavior and decision-making abilities in emergency contexts. The knowledge management-based nursing model effectively enhances treatment adherence in pulmonary TB patients in EDs. Integration of digital tools and consideration of patients' social factors strengthens nurses' roles as educators and change agents in emergency healthcare delivery.